Dynamic Editome of Zebrafish under Aminoglycosides Treatment and Its Potential Involvement in Ototoxicity - Yan, Sijia; Lu, Yulan; He, Lin; Zhao, Xinzhi; Wu, Lihua; Zhu, Huizhong; Jiang, Menglin; Su, Yu; Cao, Wei; Tian, Weidong; Xing, Qinghe (Frontiers in Pharmacology, 2017)
RNA editing is an important co- and post-transcriptional event that generates RNA and protein diversity. Aminoglycosides are a group of bactericidal antibiotics and a mainstay of antimicrobial therapy for several life-threatening infections. However, aminoglycosides can induce ototoxicity, resulting in damage to the organs responsible for hearing and balance. At low concentrations, aminoglycosides can bind to many RNA sequences and critically influence RNA editing. We used a bioinformatics approach to investigate the effect of aminoglycosides on global mRNA editing events to gain insight into the interactions between mRNA editing and aminoglycoside ototoxicity. We identified 6,850 mRNA editing sites in protein coding genes in embryonic zebrafish, and in about 10% of these, the degree of RNA editing changed more than 15% under aminoglycosides treatment. Twelve ear-development or ototoxicity related genes, including plekhm1, fgfr1a, sox9a, and calrl2, exhibited remarkable changes in mRNA editing levels in zebrafish treated with aminoglycosides. Our results indicate that aminoglycosides may have a widespread and complicated influence on the progress of mRNA editing and expression. Furthermore, these results highlight the potential importance of mRNA editing in the pathogenesis and aetiology of aminoglycoside-induced ototoxicity.